An overview of food supply chain virtualisation and granular traceability using blockchain technology. (7th August 2020) - Yadav, Jitendra; Misra, Madhvendra; Goundar, Sam
The integration of sensors and internet to the supply chain has created a new window in the supply chain management called as virtual supply chain which bears the features such as real-time tracking and monitoring of goods flow in the physical supply chain. The food supply chain is one of the delicate supply chains due to perishability, which can be due to various physical and biological factors, also the stringent safety and sustainability requirements of the product. The use of sensors and IT technology enables real-time data collection of the changes that take place in the food supply chain. The paper presents the integration of blockchain to the current virtual supply chain thus eliminating or changing the roles of intermediaries in the virtual supply chain and facilitating transparency, integrity, and authenticity of the data in the food supply chain.